Hubungan antara Kecerdasan Emosional dengan Organizational Citinzenship Behavior ditinjau dari Status Kepegawaian di Pusat Kesehatan Masyarakat (Puskesmas) Sindang Jaya - Suwandi, Zulfiani Rahmatika; fikri, Aldinel (Dinasti Research, 2025)
This study aims to examine the relationship between emotional intelligence and organizational citizenship behavior (OCB) based on employment status at the Sindang Jaya Community Health Center (Puskesmas). The research employed a quantitative approach with samples consisting of civil servant employees (PNS) and contract employees. The results indicate a positive relationship between emotional intelligence and OCB overall. However, this relationship is significant only among contract employees, while no significant relationship was found among civil servant employees. Furthermore, there was no significant difference in the relationship between emotional intelligence and OCB between civil servant and contract employees.These findings suggest that employment status influences the dynamics of the relationship between emotional intelligence and organizational citizenship behavior within the Sindang Jaya Puskesmas environment.